المهارات النفسية وعلاقتها بالتفوق الرياضي لــدى لاعبي أندية كـرة القدم في بلدية الجفرة (Faculty of Education Scientific Journal, 2025)
The current study aimed to identify the relationship between psychological skills and athletic excellence among football club players in Al-Jufra Municipality, and the level of both psychological skills and athletic excellence.The study sample consisted of all players who regularly participate in training and training, and are constantly present in the clubs, and their number is (270) players from football clubs in Al-Jufra Municipality.The researchers used a scale for each of: psychological skills, prepared by: Bell, Al-Benson and Shambrook, translated and Arabized by: Muhammad Hassan Alawi, and athletic excellence, prepared by: (Abu Mustafa, 2019).The researchers also used the following statistical methods: arithmetic averages, standard deviations, percentages, and Pearson's correlation coefficient.The results of the study showed that the field of the ability to focus attention had the highest level with an average of (3.85) and a percentage of (64%), followed by the following fields, respectively: the field of the ability to confront anxiety with an average of (3.50) and a percentage of (58%), the field of self-confidence with an average of (3.15) and a percentage of (52%), and the field of the ability to visualize with an average of (3.12) and a percentage of (52%), while the total score of the scale came with an average of (3.19) and a percentage of (53%). The results of the study also showed that the field of striving to win came in at the highest level with an average of (3.98) and a percentage of (79.6%), followed by the following fields, respectively: the field of respecting others with an average of (3.79) and a percentage of (75.8%), the field of taking responsibility with an average of (3.77) and a percentage of (75.4%), and the field of self-control with an average of (3.34) and a percentage of (66.8%), which is a high average, while the total score of the scale came in at an average of (3.72) and a percentage of (74.4). The results of the study also revealed that there is a statistically significant positive relationship at the level of (0.01) between the scores of the scale of each of the psychological skills and the athletic excellence of football players in the municipality of Al-Jufra.
Keywords: Psychological skills; athletic excellence; football players; Al-Jufra municipality